2020
DOI: 10.1002/rth2.12375
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding is increased in amyloid precursor protein knockout mouse

Abstract: Background Amyloid precursor protein (APP) is highly expressed in platelets. APP is the precursor to amyloid beta (Aβ) peptides that accumulate in cerebral amyloid angiopathy and plaques in Alzheimer disease. APP and its metabolites interact with many components of the coagulation system, and have both anticoagulant and procoagulant properties, but it is unclear if APP contributes to hemostasis in vivo. Objectives To determine whether APP contributes to hemostasis in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…It has been recurrently documented that native AMPs or AMP‐laden gels possess procoagulant attributes. [ 33,34 ] Additionally, several studies have elucidated that in Alzheimer's disease, amyloid precursor protein (APP), the antecedent to amyloid beta (Aβ) peptides, is intricately associated with the genesis of cerebral blood clots, [ 35 ] and that the formation of platelet‐reactive protein amyloid structures induces a procoagulant effect. [ 36 ] By testing the platelet activation marker CD62p, [ 36 ] we also demonstrated that all the newly designed peptides have the function of activating platelets (Figure S23, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…It has been recurrently documented that native AMPs or AMP‐laden gels possess procoagulant attributes. [ 33,34 ] Additionally, several studies have elucidated that in Alzheimer's disease, amyloid precursor protein (APP), the antecedent to amyloid beta (Aβ) peptides, is intricately associated with the genesis of cerebral blood clots, [ 35 ] and that the formation of platelet‐reactive protein amyloid structures induces a procoagulant effect. [ 36 ] By testing the platelet activation marker CD62p, [ 36 ] we also demonstrated that all the newly designed peptides have the function of activating platelets (Figure S23, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is important to consider the potential impact of these mutations on other non-vascular functions of a given protein. As an example, amyloid-β might have a physiological role in clotting 311 ; it is produced by platelets and can induce their aggregation, 87 and further influences clotting via its interactions with fibrinogen. 312 There is evidence that the Dutch and Iowa APP mutations result in altered amyloid-β interactions with fibrinogen and subsequent alterations in clot structure.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent binding partners of platelet APP following platelet activation were fibrin­(ogen), FXIII-A, and PF4, which are key proteins in hemostasis. Because APPKO mice do not appear to have a severe bleeding phenotype, APP may contribute to the nonhemostatic processes to which fibrinogen and FXIII-A also contribute, including those in inflammation and wound healing . Intracellular FXIII-A modulates the cytoskeletal proteins of platelets, such as vinculin and actin, to modulate the platelet morphology .…”
Section: Discussionmentioning
confidence: 99%